Metal–metal communication between 1, 1′-bis(diphenylphosphino)cobaltocenium and an organonickel moiety. Issue 16 (5th April 2022) - Auweiler, Daniel; Schnierle, Marc; Rapp, Valentin; Ringenberg, Mark R.
Abstract : 1, 1′-Bis(diphenylphosphino)cobaltocenium (dppc) + coordinated by dicarbonylnickel(0) or cyclopentadienylnickel(ii ), respectively, were used to understand how ligand redox is communicated to the distal metal. Abstract : 1, 1′-Bis(diphenylphosphino)cobaltocenium (dppc) +, similar to 1, 1′-bis(diphenylphosphino)ferrocene, can be coordinated by dicarbonylnickel(0) or cyclopentadienylnickel(ii ), respectively. The cyclic voltammogram of [Ni(CO)2 (dppc)] + ([1 ] + ) showed two reversible reductions, at potentails nearly identical to (dppc) + . The ligand-based reductions were confirmed by IR spectroelectrochemistry (SEC), although the Δ ν CO was larger than might be expected if the ligand was electronically decoupled to the Ni(CO)2 moiety. The larger Δ ν CO was attibuted to changes in the donor/accpetor properties of the –PPh2 moeities based on the occupation of the Co–Cp anti-bonding orbital, where the Cp ligand adopts an ylide-like structure. A similar analysis was performed on [CpNi(dppc)] 2+ ([2 ] 2+ ), where the two reductions were anodically shifted by Δ E = 292 and 520 mV from (dppc) +, indicating an increase in the M–M communication. The EPR SEC spectrum for [2 ] + showed that the cobalt was reduced, while the UV-Vis-NIR SEC spectrum for [2 ] + showed a NIR absportion at 1200 nm assinged as a MMCT Co II → Ni II band. The second reduction formed [2 ] 0 which was EPR silent but the UV-Vis-NIR SEC spectrum showed an increase in the intensity of the MMCT Co I → Ni II .